Sejarah dan Filosofi Nilai Tari Kebesaran Minahasa - Rahman, Eka Yuliana (Historia Islamica: Journal of Islamic History and Civilization, 2023)
This study aims to determine the history and philosophical value of the Minahasa kabasaran dance. This research uses a qualitative approach with a qualitative descriptive research type. Data collection techniques using observation, interviews, and document analysis. Data validation using source triangulation. The results of the study show that running the Kabasaran is an activity for carrying out ceremonies. Kabasaran was born and exists today as a conclusion from the historical journey of Minahasa. Almost every decade the condition of the Minahasa is recorded in the Kabasaran dance. The thread of the conclusion becomes a sign of every change in the face of Minahasa. This dance tells about the wars that are carried out when winning in war. This dance has a philosophical value of strength, valor of the Minahasa (Tuama) and Wuaya (courage) knights. The Kabasaran dance is equipped with spears, santi and shields in its performances. This dance is often performed at various events in North Sulawesi, both formal and non-formal. This dance is often used as soldiers to welcome guests who come to North Sulawesi.